A narrow amide I vibrational band observed by sum frequency generation spectroscopy reveals highly ordered structures of a biofilm protein at the air/water interface. Issue 14 (18th January 2016) - Wang, Zhuguang; Morales-Acosta, M. Daniela; Li, Shanghao; Liu, Wei; Kanai, Tapan; Liu, Yuting; Chen, Ya-Na; Walker, Frederick J.; Ahn, Charles H.; Leblanc, Roger M.; Yan, Elsa C. Y.
Abstract : We observed an unprecedentedly narrow amide I vibrational band from a bacterial biofilm protein at the air/water interface. Abstract : We characterized BslA, a bacterial biofilm protein, at the air/water interface using vibrational sum frequency generation spectroscopy and observed one of the sharpest amide I bands ever reported. Combining methods of surface pressure measurements, thin film X-ray reflectivity, and atomic force microscopy, we showed extremely ordered BslA at the interface.